Synthesis, cytotoxicity and antimalarial activity of ferrocenyl amides of 4-aminoquinolines - N’Da David, D; Breytenbach Jaco, C; Smith Peter, J; Lategan, Carmen (Arzneimittelforschung, 2010)
Series of 4-aminoquinolines bearing an amino side chain linked to the ferrocene moiety through an amide bond were synthesized and evaluated for their antimalarial activity against both chloro-quine-sensitive (D10, CQ-S) and chloro-quine-resistant (Dd2, CQ-R) strains of Plasmodium falciparum. They were also tested for cytotoxicity against Chinese Hamster Ovarian (CHO) cells. Amide 12 featuring propyl side chain linked to the ferrocene ring was the most active of all tested compounds. With an IC50 value of 0.08 µg/mL, this amide showed 1.5-fold higher activity than chloroquine diphosphate (IC50 = 0.12 µg/mL) against the resistant strain, with a selectivity index of 550 indicating its high selectivity towards the parasite. Derivatives which were equipotent against both strains also showed up to ten-fold increase in activity compared to primaquine.
Keywords: 4-Aminoquinolines; Antimalarial activity; Cytotoxicity; Ferrocene; Plasmodium falciparum